Jezikovne tehnologije in jezikovno načrtovanje - Stabej, Marko (Jezik in slovstvo, 2003)
On the one hand, language technologies strenghten the traditional language planning processes, i.e. the planning of the status and the corpus of the language, but on the other hand, they have other effects as well, which still need to be assessed from a sociolinguistic perspective, since they are not positive a priori. For a constructive synergie of technology and language planning, an interdisciplinary co-operation of disciplines from the fields of humanities and IT is necessary in all decisive stages of the development of language technology application.
Keywords: sociolinguistics; sociolingvistika; jezikovna politika; jezikovne tehnologije; Language technology; jezikovno načrtovanje